2014
DOI: 10.1039/c4ra09689d
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of telomerase activity in cancer cells using a label-free electrochemical impedimetric biosensing microchip

Abstract: The enzyme telomerase is present in about 85% of human cancers which makes it not only a good target for cancer treatment but also an excellent marker for cancer detection. Using a single stranded DNA probe specific for telomerase binding and reverse transcription tethered to an interdigital gold electrode array surface, the chromosome protection provided by the telomerase was replicated and followed by Electrochemical Impedance Spectroscopy as an unlabeled biosensor. Using this system designed in-house, easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…The method is simple, but the sensitivity remains to be raised to a higher level. Space-caused electrochemical probes were used to build a small biosensor microchip for real-time detection of telomerase activity in less than 20 minutes by electrochemical impedimetric biosensing 33 . Based on structure-switching DNA with ferrocene (Fc) as an electroactive indicator, space-caused electrochemical assay with a very wide linear response range, excellent stability and reproducibility was developed 34 .…”
Section: Assays For the Detection Of Telomerase Activity Using Isothementioning
confidence: 99%
“…The method is simple, but the sensitivity remains to be raised to a higher level. Space-caused electrochemical probes were used to build a small biosensor microchip for real-time detection of telomerase activity in less than 20 minutes by electrochemical impedimetric biosensing 33 . Based on structure-switching DNA with ferrocene (Fc) as an electroactive indicator, space-caused electrochemical assay with a very wide linear response range, excellent stability and reproducibility was developed 34 .…”
Section: Assays For the Detection Of Telomerase Activity Using Isothementioning
confidence: 99%
“…However, due to the intrinsic difficulty of this technique, most scientific literature limits its use to the Nyquist representation for the detection of molecules. 21…”
Section: Introductionmentioning
confidence: 99%
“…This result is in accordance with that of Cunci et al in which they reported that for the Jurkat nuclear extract, 20 min was enough time to observe a quantitatively different change in label-free impedance measurements. 23 Therefore, using the presented system, 30 min is enough time to make qualitative telomerase detection. Other modification times, 60, 120, and 180 min, showed more differences in Δ R , 3 h being the most accurate modification time for fundamental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear cell extraction was performed following an established protocol. 23 Briefly, cells were collected in the exponential phase of growth and washed twice with ice-cold PBS (140 mM NaCl, 2.7 mM KCl, 10 mM NaH 2 PO 4 , and 1.8 mM KH 2 PO 4 ). Then, the pellet was resuspended in buffer A [10 mM HEPES pH 7.9, 1.5 mM MgCl 2 , 10 mM KCl, 1 mM DTT, and 1 mM protein-sparing modified fast (PMSF)], incubated on ice for 10 min, and centrifuged at 1500 rpm for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%